2010
DOI: 10.1038/ismej.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Vibrio spp. associated with marine sponge microcosms

Abstract: Vibrio is a diverse genus of marine-associated bacteria with at least 74 species and more expected as additional marine ecospheres are interrogated. This report describes a phylogenetic reconstruction of Vibrio isolates derived from one such unique ecosystem, marine sponges (Phylum Porifera) collected from depths of 150 to 1242 feet. 16S rRNA gene sequencing along with molecular typing of 16S-23S rRNA intergenic spacer regions clustered many sponge-associated Vibrio (spp) with current known species. That is, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Wilkinson et al pioneered this effort and found a similar sponge-specific bacterial isolate that was found in 9 out of 10 sponges samples from both the Mediterranean and Great Barrier Reef [39]. Several studies have noted cultured sponge-specific isolates from many marine sponges in difference locations [40], [41]. A recent survey of the largest cultured collection of bacteria associated with marine sponges uncovered sponge specific isolates that were previously reported as “uncultured” however; nearly 88% of the isolates were dominated by the commonly cultivable class Gammaproteobacteria [42].…”
Section: Resultsmentioning
confidence: 98%
“…Wilkinson et al pioneered this effort and found a similar sponge-specific bacterial isolate that was found in 9 out of 10 sponges samples from both the Mediterranean and Great Barrier Reef [39]. Several studies have noted cultured sponge-specific isolates from many marine sponges in difference locations [40], [41]. A recent survey of the largest cultured collection of bacteria associated with marine sponges uncovered sponge specific isolates that were previously reported as “uncultured” however; nearly 88% of the isolates were dominated by the commonly cultivable class Gammaproteobacteria [42].…”
Section: Resultsmentioning
confidence: 98%
“…The absence of barriers for dispersal prevents the operation of selection for speciation and niche specialization (Oakley et al, 2010;Preheim et al, 2010). Together with the high rates of recombination of Vibrio (Vos and Didelot, 2009), these processes may constitute the major forces shaping the genetic diversity of the Vibrio populations found in marine microbiomes (Hoffmann et al, 2010;Preheim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of dispersal barriers, resident V. parahaemolyticus would be exposed to a frequent admixture with zooplankton-associated populations. This mechanism can produce constraints on niche specialization, as recently suggested for Vibrio populations from different microbiomes (Hoffmann et al, 2010;Preheim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been found to be associated with many higher organisms including fish (6), corals (7), sponges (8), hydroids (9), crabs (10), mollusks (11), and protozoa (12) (for a review of reservoirs for Vibrio cholerae see reference 13). Despite the majority of these associations being benign or beneficial, the majority of current research usually focuses on pathogenic Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%